Front Cover: Pentathiepins: A Novel Class of Glutathione Peroxidase 1 Inhibitors that Induce Oxidative Stress, Loss of Mitochondrial Membrane Potential and Apoptosis in Human Cancer Cells (ChemMedChem 16/2020). (21st August 2020) - Behnisch‐Cornwell, Steven; Bandaru, Siva Sankar Murthy; Napierkowski, Martin; Wolff, Lisa; Zubair, Muhammad; Urbainsky, Claudia; Lillig, Christopher; Schulzke, Carola; Bednarski, Patrick J.
Abstract : The Front Cover shows pentathiepins racing to block the enzyme glutathione peroxidase 1 (GPx1), a key defense of tumor cells to cytotoxic hydrogen peroxide, which forms during chemotherapy. In an allegorical depiction, the tumor planet Oncos is under attack from hydrogen peroxide bombs, but these are quickly reduced to harmless water by the defending GPx1 destroyers. However, support is on the way as a group of pentathiepin fighters moves in to neutralize GPx1 and give hydrogen peroxide a chance to destroy Oncos. Already, comets of apoptotic cancer cells are flaming into outer space. More information can be found in the Full Paper by Patrick J. Bednarski et al.